PENGARUH CITRA MEREK, KUALITAS PRODUK, DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN PRODUK SKINCARE SOMETHINC DI JAKARTA SELATAN - Madeline Alexandra Angelica Barus (2022)
This research is a quantitative study that aims to determine, analyze, and prove the influence of brand image, product quality, and price on the purchase decision of Somethinc skincare in South Jakarta. The population in this study were consumers of Something skincare in South Jakarta. Furthermore, the sample obtained was 100 respondents and the data was collected through a google form in form of questionnaire. The technique used is purposive sampling with descriptive analysis and inferential analysis. The data is processed using a tool called SmartPLS 4.0. Then, the hypothesis testing that has been obtained from this study is as follows, (1) there is a positive and significant influence between the brand image on purchasing decisions which has an effect of 0.380, (2) there is a positive influence and significant between product quality on purchasing decisions which have an effect of 0.396, (3) there is a positive and not significant effect between price on purchasing decisions which influence 0.112. The contribution from the variable brand image, product quality, and price together amounted to 0.699 or 69.9% while the rest was caused by other factors outside this study.